2020
DOI: 10.1128/msystems.00389-20
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Structural Basis of Synthesis of the Unique Intermediate Dehydro-F 420 -0 in Mycobacteria

Abstract: F420 is a low-potential redox cofactor used by diverse bacteria and archaea. In mycobacteria, this cofactor has multiple roles, including adaptation to redox stress, cell wall biosynthesis, and activation of the clinical antitubercular prodrugs pretomanid and delamanid. A recent biochemical study proposed a revised biosynthesis pathway for F420 in mycobacteria; it was suggested that phosphoenolpyruvate served as a metabolic precursor for this pathway, rather than 2-phospholactate as long proposed, but these fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…A follow-up study delivered further evidence supporting the biosynthetic route via DF 420 in mycobacteria. The authors showed the formation of DF 420 from PEP in cell extracts of M. smegmatis and could reveal strong binding of DF 420 to the active site of FbiA (CofD) by X-ray crystallographic studies of the enzyme ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up study delivered further evidence supporting the biosynthetic route via DF 420 in mycobacteria. The authors showed the formation of DF 420 from PEP in cell extracts of M. smegmatis and could reveal strong binding of DF 420 to the active site of FbiA (CofD) by X-ray crystallographic studies of the enzyme ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Step 7. Through distinct enzymatic reactions mediated by FbiC, FbiB and FbiA, 5-A-RU can also be converted to F 420 (57). DMRL and its derivatives can act as MAIT cell activators.…”
Section: Resultsmentioning
confidence: 99%
“…S1A in the supplemental material). Based on prior experimental evidence ( 14 17 ), it is expected that the constructed M. tuberculosis Δ mftD is most likely mycofactocin deficient, thereby resembling impaired F 420 synthesis in a Mycobacterium smegmatis strain lacking either of the F 420 biosynthesis genes ( 19 ). As such, disruption of mftD had no impact on M. tuberculosis H37Rv growth on glycerol-supplemented Middlebrook 7H9 (m7H9) medium under well-aerated conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mftD -encoded product catalyzes the crucial step in formation of premycofactocin—a penultimate biosynthetic intermediate, which could oxidize NADH, and its calculated midpoint potential is ≈−255 mV ( 14 ). Another noncanonical cofactor is F 420 , which is generated through the aerobic route with relatively lower redox potential in mycobacterial species but facilitates M. tuberculosis microaerophilic adaptation ( 19 , 40 42 ). F 420 cofactor recycling in methanogenic (anaerobic) archaea is achieved by F 420 reductase (Fno), which transfers electrons between F 420 and NADPH pools.…”
Section: Discussionmentioning
confidence: 99%